2022
DOI: 10.3389/fimmu.2022.842745
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms (SNP) and SNP-SNP Interactions of the Surfactant Protein Genes Are Associated With Idiopathic Pulmonary Fibrosis in a Mexican Study Group; Comparison With Hypersensitivity Pneumonitis

Abstract: Surfactant proteins (SPs) are important for normal lung function and innate immunity of the lungs and their genes have been identified with significant genetic variability. Changes in quantity or quality of SPs due to genetic mutations or natural genetic variability may alter their functions and contribute to the host susceptibility for particular diseases. Alternatively, SP single nucleotide polymorphisms (SNPs) can serve as markers to identify disease risk or response to therapies, as shown for other genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…A total of 16 target SNPs of SP genes, SFTPA1 , SFTPA2 , SFTPB , SFTPC , and SFTPD were selected that included, 5 SNPs from SFTPA1 , rs1059047, rs1136450, rs1136451, rs1059057, and rs4253527; 4 SNPs from SFTPA2 , rs1059046, rs17886395, rs1965707, and 1965708; 3 SNPs from SFTPB , rs2077079, rs3024798, and rs1130866; 2 SNPs from SFTPC , rs4715 and rs1124; and 2 SNPs from SFTPD , rs721917 and rs2243639. Several acute and chronic pulmonary diseases of all age groups, such as, neonatal RDS ( 31 35 ), CF ( 36 ), COPD ( 37 , 38 ), ARDS ( 23 ), hypersensitivity pneumonitis ( 39 , 40 ), pediatric ARF ( 41 ), and persistent respiratory morbidity in pediatric ARF survivors ( 42 ) have been shown to be associated with the studied SNPs. The SP-A1 (6A, 6A m , m=0-13) and SP-A2 (1A, 1A n , n=0-15) genotypes were assigned as described ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 16 target SNPs of SP genes, SFTPA1 , SFTPA2 , SFTPB , SFTPC , and SFTPD were selected that included, 5 SNPs from SFTPA1 , rs1059047, rs1136450, rs1136451, rs1059057, and rs4253527; 4 SNPs from SFTPA2 , rs1059046, rs17886395, rs1965707, and 1965708; 3 SNPs from SFTPB , rs2077079, rs3024798, and rs1130866; 2 SNPs from SFTPC , rs4715 and rs1124; and 2 SNPs from SFTPD , rs721917 and rs2243639. Several acute and chronic pulmonary diseases of all age groups, such as, neonatal RDS ( 31 35 ), CF ( 36 ), COPD ( 37 , 38 ), ARDS ( 23 ), hypersensitivity pneumonitis ( 39 , 40 ), pediatric ARF ( 41 ), and persistent respiratory morbidity in pediatric ARF survivors ( 42 ) have been shown to be associated with the studied SNPs. The SP-A1 (6A, 6A m , m=0-13) and SP-A2 (1A, 1A n , n=0-15) genotypes were assigned as described ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several acute and chronic pulmonary diseases of all age groups, such as, neonatal RDS (31)(32)(33)(34)(35), CF (36), COPD (37,38), ARDS (23), hypersensitivity pneumonitis (39,40), pediatric ARF (41), and persistent respiratory morbidity in pediatric ARF survivors (42) have been shown to be associated with the studied SNPs. The SP-A1 (6A, 6A m , m=0-13) and SP-A2 (1A, 1A n , n=0-15) genotypes were assigned as described (19).…”
Section: Selection Of Genetic Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These SNPs were selected because of their associations with several acute and chronic pulmonary diseases. 7,[9][10][11]14,15 The SP-A1 (6A, 6A m , m = 0-13) and SP-A2 (1A, 1A n , n = 0-15) genotypes were assigned as described. 6…”
Section: Dna Isolation and Selection Of Genetic Variantsmentioning
confidence: 99%
“…3 Multiple single-nucleotide polymorphisms (SNPs) have been identified for each of these genes. [4][5][6] These SNPs have been shown to associate with various acute and chronic pulmonary diseases, such as cystic fibrosis, 7 acute respiratory distress syndrome, 8 neonatal respiratory distress syndrome (RDS), 9 hypersensitivity pneumonitis, 10 interstitial pulmonary fibrosis, 11 the severity of respiratory syncytial virus (RSV) 12 and tuberculosis (TB). 13 We showed that SNP-SNP interactions among SP genes are associated with pediatric ARF and its short- 14 and long-term outcomes.…”
mentioning
confidence: 99%